Only troncoconical cuffs can provide accurate blood pressure measurements in people with severe obesity. Issue 1 (January 2019) - Palatini, Paolo; Benetti, Elisabetta; Fania, Claudio; Saladini, Francesca
Abstract : Objective: Rectangular (cylindrical) cuffs and bladders are currently used for blood pressure (BP) measurement at the upper arm. However, large arms have a troncoconical shape, which make cylindrical cuffs potentially unsuitable. Aim of this study was to investigate the effect of the shape of the cuff on BP measurement in very obese participants. Methods: In 33 participants with upper arm mid-circumference at least 42 cm and 33 participants of control, cylindrical and troncoconical cuffs of appropriate size were compared. In addition, in the obese participants, the pressure transmitted to the arm under the cuffs was measured at five cuff pressure levels using a paper-thin pressure sensor. Results: In all obese participants, the upper arm shape was troncoconical (mean ± SD slant angle, 84.1 ± 1.4°). In this group, SBP and DBP differences between the troncoconical and the cylindrical cuff were −5.3 ± 4.0 and −3.0 ± 4.3 mmHg, respectively ( P  < 0.001/=0.01 versus controls). In the obese participants of the top BP quintile, the between-cuff SBP difference was −9.1 ± 5.1 mmHg. Arm slant angle was an independent predictor of the between-cuff SBP discrepancy ( P  = 0.003). When the cylindrical cuff was used, measurement with the pressure sensor showed a marked disagreement between the pressure in the cuff and the pressure transmitted to the arm (mean difference, −10.2 ± 5.2 mmHg) a difference, which increased with increasing level of the pressure pumped in the cuff. Conclusion: In very obese people, cylindrical cuffs overestimate BP chiefly in people with high SBP and thus only troncoconical cuffs should be used. Abstract : Supplemental Digital Content is available in the text